Penerapan Asas The Binding Persuasive of Precedent Terhadap Pidana Di Bawah Ketentuan Minimum Khusus Dalam Tindak Pidana Narkotika - Dayang Debby Aulia Hakim; Ivan Zairani Lisi; Orin Gusta Andini (Jurnal Risalah Hukum, 2021)
Narcotics crimes include crimes outside the Criminal Code which are regulated in the Narcotics Law Number 35 of 2009 and therein regulates special minimum sentence provisions. The approach used is a doctrinal approach with the aim of knowing two main points of discussion: First, the author wants to know and understand the punishment for narcotics crimes that are criminalized under a special minimum sentence. Second, the author wants to know the implementation of the binding persuasive principle of precedent in the judge's consideration in deciding narcotics crime cases under a special minimum sentence. Based on the results of the study, it can be concluded that the punishment of narcotics crimes that are sentenced under the special minimum provisions are not in accordance with the special minimum sentence provisions in the Narcotics Law, causing legal uncertainty. Then legal certainty and the principle of the binding persuasive of precedent cannot be applied because the judge uses his freedom in imposing a sentence by imposing a sentence under a special minimum provision. Keywords: the binding persuasive of precedent principle; judge’s consideration; minimum sentence.